Global managerial skill-sets, management development, and the role of HR: An exploratory qualitative study with North American and Indian managers - Ananthram, Subramaniam; Nankervis, Alan (Academy of Taiwan Information Systems Research, 2013)
Ever since Porter’s (1986) seminal study, much research has focused on the key factors which assure competitiveness in increasingly global marketplaces, including both business and human resource management (HRM) strategies. With respect to the latter, the importance of management development in developing managers with global skills-sets has been a persistent theme in the literature on competitive strategy and HRM over the last decade. This paper extends such research by employing a qualitative methodology to explore the need for and identify these global skills-sets from the perspectives of fifty-six senior executives from multinational organizations in North America and India. The role of human resource (HR) departments in developing the identified skill-sets in both contexts is discussed by identifying its role in management development. The paper also presents the implications for HR professionals and practitioners and provides suggestions for future research.